Functional comparison of human Adenomatous Polyposis Coli (APC) and APC-like in targeting beta-catenin for degradation - Schneikert, Jean (2013)
Truncating mutations affect the adenomatous polyposis coli (APC) gene in most cases of colon cancer, resulting in the stabilization of β-catenin and uncontrolled cell proliferation. We show here that colon cancer cell lines express also the paralog APC-like (APCL or APC2). RNA interference revealed that it controls the level and/or the activity of β-catenin, but it is less efficient and binds less well to β-catenin than APC, thereby providing one explanation as to why the gene is not mutated in colon cancer. A further comparison indicates that APCL down-regulates the β-catenin level despite the lack of the 15R region known to be important in APC. To understand this discrepancy, we performed immunoprecipitation experiments that revealed that phosphorylated β-catenin displays a preference for binding to the 15 amino acid repeats (15R) rather than the first 20 amino acid repeat of APC. This suggests that the 15R region constitutes a gate connecting the steps of β-catenin phosphorylation and subsequent ubiquitination/degradation. Using RNA interference and domain swapping experiments, we show that APCL benefits from the 15R of truncated APC to target β-catenin for degradation, in a process likely involving heterodimerization of the two partners. Our data suggest that the functional complementation of APCL by APC constitutes a substantial facet of tumour development, because the truncating mutations of APC in colorectal tumours from familial adenomatous polyposis (FAP) patients are almost always selected for the retention of at least one 15R.